Contaminating dreams and resistances: The house, the screen and the between (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article approaches some creative and pedagogical aspects of the experience of the workshop "Only Dreams Don’t Fear the Contagion", accomplished by Núcleo Fuga! In online form in the context of the COVID 19 pandemic. Regarding the study of presence in this remote mode, we explore some proposals triggered by the ideas of contagion and belonging, in a practice based on Klauss Vianna Technique of dance and somatic education and on performative programs, jointed to cartographic practices. In the creative study of the compositions with the environment of the house, the proposals aimed  performative possibilities by visiting the enigma-images of dreams, as a tension to provoke the relationship between art, the unconscious and resistance.
Keywords: Performative programs; Cartographic practices; Klauss Vianna Technique; Dreams; Resistance